Primary care faecal calprotectin testing in children with suspected inflammatory bowel disease: a diagnostic accuracy study. Issue 10 (18th May 2020) - Walker, Gareth J; Chanchlani, Neil; Thomas, Amanda; Lin, Simeng; Moore, Lucy; Heerasing, Neel M; Hendy, Peter; Abdelrahim, Mohamed; Mole, Sean; Perry, Mandy H; Mcdonald, Timothy J; Bewshea, Claire M; et al.
Abstract : Objective: To determine the diagnostic accuracy of calprotectin to diagnose inflammatory bowel disease (IBD) in children in whom general practitioners (GPs) suspected IBD. Design: Prospective observational cohort study of a new calprotectin-based primary care referral pathway. Setting: 48 GP practices and gastroenterology secondary care services at the Royal Devon and Exeter NHS Foundation Trust in the South-West of England, UK. Patients: 195 children aged between 4 and 18 years referred on the pathway between January 2014 and August 2017 for investigation of gastrointestinal symptoms were included. Interventions: Primary-care-driven faecal calprotectin testing. Primary and secondary care records over 12 months from the point of calprotectin testing were used as the reference standard. Main outcome measures: Diagnostic accuracy of calprotectin testing to detect IBD. Results: 7% (13/195) tested patients were diagnosed with IBD. Using our prespecified cut-off of 100 µg/g, calprotectin had a diagnostic accuracy of 91% (95% CI 86% to 95%) with a sensitivity for distinguishing IBD from non-IBD of 100% (95% CI 75% to 100%), a specificity of 91% (95% CI 85% to 94%), a positive predictive value of 43% (95% CI 25% to 63%) and a negative predictive value of 100% (95% CI 98% to 100%). Calprotectin testing had no effect on the time to diagnosis, but a negative test contributed to saved referrals and was associated with fewer diagnostic tests in secondary care. Conclusions: Calprotectin testing of children with suspected IBD in primary care accurately distinguishes IBD from a functional gut disorder, reduces secondary care referrals and associated diagnostic healthcare utilisation.